Empowering Workers' Safety Knowledge for Effective Accident Prevention in Sanitary Industry, Malang - Rubayat Indradi; Iqbal Agung Nugroho; Febri Endra Budi Setyawan; Feny Tunjungsari; Mochammad Aleq Sander (International Journal Labs, 2025)
People work in various types of jobs, such as foremen, labourers, farmers, etc.; they can encounter accidents at their workplace, and sometimes it may become a liability if someone gets hurt. One of these injuries is blunt trauma, which results from a mechanical force generated by a blunt object that interacts over some area. Most factory workers in these industries have experienced a history of occupational accidents, especially blunt trauma (up to 60% of overall workers in this workplace) in the Karangbesuki Sanitary Industry Center, Malang. Therefore, being able to quickly understand what workplace safety entails is important to promote safety; however, this knowledge may be quite limited when dealing with accident prevention. This article is intended to analyze the influence of occupational safety knowledge on efforts to prevent blunt trauma workplace accidents in the Sanitary Industry Center of Karangbesuki in Malang City. This was a descriptive cross-sectional study involving 42 workers at the Karangbesuki Sanitary Industry in Malang City. Data collection was carried out through the distribution of questionnaires. The analysis of the data was conducted using IBM SPSS (Statistical Package for the Social Sciences) software. Occupational safety knowledge has a significant effect on the incidence of blunt trauma workplace events, with the result that the probability is 0.00 < 0.05. It can be concluded that knowledge of occupational safety is very necessary so that incidents of blunt trauma in the workplace at the Sanitary Industry Center, Karangbesuki, Malang City, do not occur.